2019
DOI: 10.1038/s41598-019-56417-8
|View full text |Cite
|
Sign up to set email alerts
|

Circular METRN RNA hsa_circ_0037251 Promotes Glioma Progression by Sponging miR-1229-3p and Regulating mTOR Expression

Abstract: Circular RNAs (circRNAs) are a newly identifed non-coding RNA in many cellular processes and tumours. This study aimed to investigate the role of hsa_circ_0037251, one circRNA generated from several exons of the gene termed METRN, in glioma progression. Through in vitro experiments, we discovered that high expression of hsa_circ_0037251 was related to low expression of the microRNA miR-1229-3p and high expression of mTOR. The over-expressed hsa_circ_0037251 promoted cell proliferation, invasion and migration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…Meanwhile, circ-0006948 enhances HMGA2 expression by sponging miR-490-3p, thus inducing EMT and aggravating ESCC [ 6 ]. In addition, circ-0037251 affects glioma cell proliferation and metastasis by regulating the miR-1229-3p/mTOR axis [ 7 ]. CircPIP5K1A is a newly discovered cancer-related circRNA, which is a powerful regulator in tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, circ-0006948 enhances HMGA2 expression by sponging miR-490-3p, thus inducing EMT and aggravating ESCC [ 6 ]. In addition, circ-0037251 affects glioma cell proliferation and metastasis by regulating the miR-1229-3p/mTOR axis [ 7 ]. CircPIP5K1A is a newly discovered cancer-related circRNA, which is a powerful regulator in tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The most common function of circRNAs is to act as miRNA sponges in the regulation of the cell signaling pathway. For example, Cao et al found that hsa_circ_0037251 enhanced the progression of glioma via sponging miR-1229-3p [ 9 ]. Moreover, circRNAs can also engage in other cell activities.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of circSMARCA5 inhibits the proliferation and migration of HCC cells (Li Z. et al, 2019). CircPTGR1 promoted HCC progression via the miR-449a/MET pathway and its knockdown reduced HCC progression Wang G. et al, 2019). CircRHOT1 facilitated HCC progression by recruiting TIP60, a histone acetyltransferase to the nuclear orphan receptor NR2F6 promoter to enhance its expression (Wang L. et al, 2019).…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%
“…Downregulation of cZNF292 reduced proliferation in GBM cells and suppressed human glioma tube formation by modulating Wnt/β-catenin signaling pathway (Yang P. et al, 2019). Circ_0037251 enhances GBM progression by sponging miR-1229-3p and upregulating mTOR (Cao et al, 2019). Knockdown of circ_0037251 inhibited the expression of mTOR leading to increased apoptosis and promoting cell-cycle arrest (Cao et al, 2019).…”
Section: Glioblastoma (Gbm)mentioning
confidence: 99%
See 1 more Smart Citation